The AWSOM Correlation In Comparative Bantu Object Marking - van der Wal, Jenneke (My University, 2019)
The Bantu languages show much variation in object marking, two parameters being (1) their behaviour in ditransitives (symmetric or asymmetric) and (2) the number of object markers allowed (single or multiple). This paper reveals that a combination of these parameter settings in a sample of 50+ Bantu languages results in an almost-gap, the AWSOM correlation: “asymmetry wants single object marking”. A Minimalist featural analysis is presented of Bantu object marking as agreement with a defective goal (van der Wal 2015) and parametric variation in the distribution of φ features on low functional heads (e.g. Appl) accounts for both the AWSOM and Sambaa as the one exception to the AWSOM.
Keywords: HUMANITIES and RELIGION::Languages and linguistics::Other languages::Bantu languages; object marking; AWSOM correlation